2017
DOI: 10.1186/s12876-017-0666-x
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution manometry in patients with and without globus pharyngeus and/or symptoms of laryngopharyngeal reflux

Abstract: BackgroundGlobus pharyngeus is common and has a low cure rate. Its etiology is complex and reported to be associated with laryngopharyngeal reflux (LPR). However, some patients with globus do not exhibit any reflux symptoms or respond to proton pump inhibitors (PPIs) treatments. The purpose of this study was to clarify the related risk factors of these patients with a final objective of improving the curative effect.MethodsForty two patients afflicted with globus pharyngeus (G group) and 38 patients without gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Gastroenterology research has focused largely on investigating the association of GERD with globus symptoms using manometry and dual‐channel impedance studies. Although these studies have established a correlation between GERD and globus, no causal relationship has been established, particularly when focusing on extraesophageal reflux symptoms and findings . The otolaryngology approach to globus pharyngeus is somewhat distinct from that of gastroenterologists because otolaryngologists rule out oropharyngeal, laryngeal, and upper aerodigestive malignancy, although multiple recent studies have shown an exceedingly low likelihood of malignancy in patients with typical globus symptoms .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gastroenterology research has focused largely on investigating the association of GERD with globus symptoms using manometry and dual‐channel impedance studies. Although these studies have established a correlation between GERD and globus, no causal relationship has been established, particularly when focusing on extraesophageal reflux symptoms and findings . The otolaryngology approach to globus pharyngeus is somewhat distinct from that of gastroenterologists because otolaryngologists rule out oropharyngeal, laryngeal, and upper aerodigestive malignancy, although multiple recent studies have shown an exceedingly low likelihood of malignancy in patients with typical globus symptoms .…”
Section: Discussionmentioning
confidence: 99%
“…Although these studies have established a correlation between GERD and globus, no causal relationship has been established, particularly when focusing on extraesophageal reflux symptoms and findings. 11,12 The otolaryngology approach to globus pharyngeus is somewhat distinct from that of gastroenterologists because otolaryngologists rule out oropharyngeal, laryngeal, and upper aerodigestive malignancy, although multiple recent studies have shown an exceedingly low likelihood of malignancy in patients with typical globus symptoms. 10,13,14 A retrospective review of 250 cases of rigid endoscopy performed for primary globus failed to reveal any malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…The catheter was then fixed with tape to the patient's nose followed with a 5‐minutes period of adaptation. The HRM recording was made in the supine position with a 30‐sec basal period with no deglutition in order to obtain the sphincter resting pressures, followed by a total of ten water (5 mL) swallows at 30 sec intervals seconds .…”
Section: Methodsmentioning
confidence: 99%
“…Esophageal motor abnormalities, particularly pertaining to the upper esophageal sphincter (UES) have been described in globus, but it remains unclear if the findings are causative of the symptom, or a consequence of concurrent anxiety. A reactive, hyperdynamic UES with respiration, 21 high UES resting pressures, 22 and elevated UES postswallow residual pressures 23,24 have been reported. There are limited data demonstrating that a lowering of UES pressure with neuromodulator therapy (paroxetine and amitriptyline) can be associated with improvement in globus symptoms 25 .…”
Section: Etiology Of Globusmentioning
confidence: 97%